Interactive Learning Media Using Articulate Storyline 3 in Minang Kabau Culture Cours in Informastic And Computer Engineering Education IAIN Bukit Tinggi - Ahmad Baqi (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2022)
This research is motivated by learning Minangkabau Culture which in general the material is only in the form of delivering papers with the lecture method. In its delivery, lecturers use minimal learning media in class and the use of adequate technological facilities is still underutilized by lecturers so that boring learning methods have an impact on student interest in learning to be low. This study uses the Research And Development (R&D) method using the 4D version approach, namely Define, Design, Develop, and Disseminate. using Luther Sutopo's multimedia development model which consists of 6 stages, namely concept, design, collecting material, assembly, testing and distribution. The product test used in this study is the validity test using the Aiken's "v" formula, the practicality test using the Moment Kappa formula, and the effectiveness test using the Gain Score formula. Based on the three tests, it was found that the product was valid with a value of 0.88, practical with a value of 0.94 and effective with a value of 0.87. This product can make it easier for students to understand and repeat the material that has been conveyed by the lecturer and make it easier for the lecturer to deliver learning material so that the lecture process becomes valid, practical and effective.